IMPLEMENTATION OF LEARNING BASED ON THE SCIENTIFIC APPROACH OF FINE ARTS MAPEL PRESENTATION SLIDE PAINTING METHOD APPLICABLE POINTILIST ENGINEERING - Billy Eka Wardana; Dr. Imam Mawardi, M.Ag. (Sean Institute, 2022)
This study aims to find out a description of the implementation of art and culture learning in visual arts based on a scientific approach with a slide presentation of the applied painting method of pointillism techniques at SMP KARTIKA Xii-1 Mertoyudan, Magelang Regency. The method used in this study is a qualitative descriptive method. This is an art and culture teacher at SMP KARTIKA Xii-1 Mertoyudan, Magelang Regency. The data collection technique used observation, interview, and documentation techniques. The research instruments used were observation guidelines and interview guidelines. The data analysis technique used is an analytical technique which includes data reduction, data presentation, as well as drawing conclusions and verification. Testing the validity of the data is carried out through credibility testing with triangulation of techniques and sources. The results of student achievement are still found by students who have not reached the KKM. Based on these conditions, the researcher intends to conduct research in the form of Classroom Action Research with the material Efforts to Improve Learning Achievement of Cultural Arts Materials for Applied Painting Using Pointillism Techniques for Class IX A SMP KARTIKA Xii-1 Mertoyudan, Kab. Magelang. The number of students in Class IX A is 25 students. From the results of the implementation of 3 cycles in ptk using the pointillism technique, it is able to increase student achievement by about 56% from the initial conditions of the study. from the initial conditions to the first cycle of 36% (10 students), the first cycle to the second cycle of 20% (14 students), while from the initial condition before the action to cycle II and cycle III of 56% (25 students). The learning outcomes in cycle 2 are: there are no students who score less than the KKM, and 25 children (100%) get a score equal to / exceed the KKM. Cycle 3 (100%).